Tripartite relationship of urban planning, city growth, and health for sustainable development in Akure, Nigeria - Bayode, Taye; Siegmund, Alexander (Frontiers in Sustainable Cities, 2024)
We live in an urban planet. As the world continues to urbanize, urban development that support the health and wellbeing of city dwellers is far more important than ever before to achieve sustainable development targets. This study explores the complex relationship among urban planning, city growth, and health as critical drivers of sustainable development in the rapidly growing nodal city of Akure, Nigeria. The study provides a four-decade spatio-temporal model of urban Land Use Land Cover (LULC) changes in Akure between the years 1984 and 2023 from acquired Landsat satellite imageries. The result shows more than 20% net change increase in developed LULC classes between the study years. A strong positive correlation exists between the years covered in the analyses and urban development (r = 0.93, p = 0.002), and a strong negative relationship with the forest land use (r = −0.94, p = 0.002) with potential debilitating impacts on residents’ health, green infrastructures and the city’s sustainability in the future. Furthermore, results of key informant interviews (KIIs) of officials of the Ministry of Physical Planning and Urban Development (MPPUD) in Akure, Ondo State, unveil various views on the “place of health” in urban planning practices in Akure. A lack of synergy between urban planners and public health practitioners in the city and limiting scope of functions of urban planning on the impact of health in Akure were observed. Thus, we recommend the integration of a sustainable urban planning approach as a guide to manage the city.